2015
DOI: 10.1016/j.gca.2014.09.014
|View full text |Cite
|
Sign up to set email alerts
|

The paradox between low shock-stage and evidence for compaction in CM carbonaceous chondrites explained by multiple low-intensity impacts

Abstract: Petrographic analysis of eight CM carbonaceous chondrites (EET 96029, LAP 031166, LON 94101, MET 01072, Murchison, Murray, SCO 06043, QUE 93005) by electron imaging and diffraction, and X-ray computed tomography, reveals that six of them have a petrofabric defined by shock flattened chondrules. With the exception of Murchison, those CMs that have a strong petrofabric also contain open or mineralized fractures, indicating that tensional stresses accompanying the impacts were sufficient to locally exceed the yie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
81
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(97 citation statements)
references
References 62 publications
15
81
1
Order By: Relevance
“…This classification is consistent with Lindgren et al. (), who estimated that its pair, MET 01072, has a petrologic subtype of CM2.3. From the concentration of H in water/OH, Alexander et al.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This classification is consistent with Lindgren et al. (), who estimated that its pair, MET 01072, has a petrologic subtype of CM2.3. From the concentration of H in water/OH, Alexander et al.…”
Section: Discussionsupporting
confidence: 92%
“…) and so did not experience high impact pressures, the petrofabrics could have formed from one or more lower intensity collisions (Lindgren et al. ). There are, however, no clear petrographic indicators of whether impact compaction took place before, during, or after aqueous alteration.…”
Section: Discussionmentioning
confidence: 99%
“…; Rubin ; Lindgren et al. ). Although alteration has been shown to clearly predate brecciation in a few cases (Metzler et al.…”
Section: Introductionmentioning
confidence: 99%
“…; Rubin and Swindle ; Lindgren et al. ; Ruzicka and Hugo ); the latter seemingly in contrast with the low shock stage classifications (S1–S2) of many of the studied chondrites. This paradox is resolved by the results of matrix‐based structural studies (Scott et al.…”
Section: Introductionmentioning
confidence: 75%
“…Nevertheless, an essential feature in rock deformation is conspicuously absent in the list of shock criteria in meteorites: Preferred orientation fabrics, such as shape-preferred orientation (SPO) involving the orientation of the grains themselves and lattice-preferred orientation (LPO) involving the slip of specific crystallographic planes in a preferred direction. Several structural studies of chondrites have identified deformed chondrules and grain alignment fabrics and have attributed these to burial (Cain et al 1986;Zolensky et al 1997) or shock impact (Scott et al 1992;Rubin and Swindle 2011;Lindgren et al 2015;Ruzicka and Hugo 2018); the latter seemingly in contrast with the low shock stage classifications (S1-S2) of many of the studied chondrites. This paradox is resolved by the results of matrix-based structural studies (Scott et al 1992;Nakamura et al 1995;Watt et al 2006;Forman et al 2016Forman et al , 2017 concluding that chondrule deformation and alignment occurs through impact-induced reduction in matrix porosity through pore collapse with consequential matrix compaction.…”
Section: Introductionmentioning
confidence: 98%